GAMBARAN KUALITAS TIDUR IBU HAMIL TRIMESTER 3 - Dehana Ornela Vonty Gultom; Kamsatun Kamsatun; Susi Kusniasih; Iryanti Iryanti (Jurnal Kesehatan Siliwangi, 2020)
The National Sleep Foundation states that 97.3% of third trimester pregnant women always wake up at night and on average about 78% of pregnant women in America experience sleep disorders. Sleep disorders during pregnancy occur during the first trimester as much as 13% to 80% and third trimester as much as 66% to 97% while in Indonesia pregnant women in the third trimester as much as 97% experience sleep disorders. Third trimester pregnant women often experience complaints of sleep / rest due to physiological, psychological and disease changes. Sleep disturbance can cause fatigue in pregnant women which adversely affects the body condition of the mother, the baby in the womb and later labor and diseases that interfere with sleep breaks. Therefore this study aims to determine the sleep quality of third trimester pregnant women. This type of research is a descriptive study with a literature review (SLR) method. Secondary data collection techniques with three journal samples. The results showed an illustration of poor quality trimester III pregnant women, journal 1 (52.8%) 19 pregnant women, journal 2 (36.7%) 9 pregnant women and journal 3 (56.5%) 13 pregnant women. It can be concluded that the sleep quality of trimester III pregnant women is categorized as poor due to physiological, psychological and disease factors namely frequent urination at night, illness, anxiety before delivery, and experiencing changes in blood pressure at risk of complications of pregnancy. Recommendations to health care institutions to make effective promotive and preventive actions. One of the methods is counseling by health workers during ANC examination regarding sleep breaks and pregnancy exercises for pregnant women in the Puskesmas target area. Thus pregnant women get adequate and good quality sleep.